2007
DOI: 10.3168/jds.2007-0023
|View full text |Cite
|
Sign up to set email alerts
|

Body Condition Score and Body Weight Effects on Dystocia and Stillbirths and Consequent Effects on Postcalving Performance

Abstract: The objective of this study was to quantify the effect of periparturient body condition score (BCS) and body weight (BW) related traits on the incidence of calving dystocia and stillbirths, and to determine any consequent effect of dystocia and stillbirths on BCS, BW, milk production, udder health, and fertility in grazing Holstein-Friesian dairy cows. Up to 2,384 lactation records with data on calving dystocia or stillbirths were available from one research herd across 15 yr. Mixed models and generalized esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
137
9
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(186 citation statements)
references
References 32 publications
30
137
9
4
Order By: Relevance
“…The likelihood of perinatal mortality was approximately 3-times as high in primiparae compared with pluriparae, a finding similar to the range (1.5 to 2.6) reported previously (Szenci and Kiss, 1982;Steinbock et al, 2003;Berry et al, 2007), indicating that perinatal mortality is a different trait in younger and older cows. While most of this differential is attributable to the significant interaction between parity and calving assistance rate shown here, recent research in sheep has shown that first parity animals had smaller and less efficient placentas resulting in less viable lambs than those of older sheep (Dwyer et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The likelihood of perinatal mortality was approximately 3-times as high in primiparae compared with pluriparae, a finding similar to the range (1.5 to 2.6) reported previously (Szenci and Kiss, 1982;Steinbock et al, 2003;Berry et al, 2007), indicating that perinatal mortality is a different trait in younger and older cows. While most of this differential is attributable to the significant interaction between parity and calving assistance rate shown here, recent research in sheep has shown that first parity animals had smaller and less efficient placentas resulting in less viable lambs than those of older sheep (Dwyer et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…The odds ratios found here are within the wide range (2.7 to 14.6) reported for the effects of calving assistance on perinatal mortality in dairy herds (Chassagne et al, 1999;Johanson and Berger 2003;Berry et al, 2007). While dystocia is often listed as the most significant risk factor for perinatal mortality, the results of the present study and of others (McGuirk et al, 1999;Meyer et al, 2001;Sorge, 2005) show that even slight calving assistance is associated with increased risk of perinatal mortality.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Appropriate feeding of the dry cow (Mulligan and Doherty, 2008), calving facilities and calving management are all essential to optimizing the health of newborn calves (Gulliksen et al, 2009a). Over or underfeeding the dry cow influences her body condition score (BCS), changes in which may lead to a greater incidence of dystocia (Berry et al, 2007) thus appropriate nutrition of the dry cow is crucial. In addition to dry cow nutrition, monitoring of the cow around calving is important for successful healthy calf births (Lombard et al, 2007).…”
mentioning
confidence: 99%